Factors Associated with the Retinal Nerve Fiber Layer Loss after Acute Primary Angle Closure: A Prospective EDI-OCT Study. - Eun Ji Lee; Tae-Woo Kim; Kyoung Min Lee; Seung Hyen Lee; Hyunjoong Kim (PLoS ONE)
Purpose To determine the factors associated with retinal nerve fiber layer (RNFL) loss in eyes with acute primary angle-closure (APAC), particularly focusing on the influence of the change in the anterior lamina cribrosa surface depth (LCD). Methods After the initial presentation, 30 eyes with unilateral APAC were followed up at the following specific time points over a 12-month period: 1 week, 1~2 months, 2~3 months, 5~6 months, and 11~12 months. These follow-ups involved intraocular pressure measurements, enhanced depth-imaging spectral-domain optical coherence tomography (SD-OCT) scanning of the optic disc, and measurements of the circumpapillary RNFL thickness. The prelaminar tissue thickness (PLT) and LCD were determined in the SD-OCT images obtained at each follow-up visit. Results Repeated measures analysis of variance revealed a significant pattern of decrease in the global RNFL thickness, PLT, and LCD (all p<0.001). The global RNFL thickness decreased continuously throughout the follow-up period, while the PLT decreased until 5~6 months and did not change thereafter. The LCD reduced until 2~3 months and then also remained steady. Multivariable regression analysis revealed that symptoms with a longer duration before receiving laser peripheral iridotomy (LI) (p = 0.049) and a larger LCD reduction (p = 0.034) were significant factors associated with the conversion to an abnormal RNFL thickness defined using OCT normative data. Conclusion Early short-term decreases in the PLT and LCD and overall long-term decrease in the peripapillary RNFL were observed during a 12-month follow-up after an APAC episode. A longer duration of symptoms before receiving LI treatment and larger LCD reduction during follow-up were associated with the progressive RNFL loss. The LCD reduction may indicate a prior presence of significant pressure-induced stress that had been imposed on the optic nerve head at the time of APAC episode. Glaucomatous progression should be suspected in eyes showing LCD reduction after the APAC remission.